Thursday

April 17, 2014

April 17, 2014

Posted by **Sean** on Wednesday, March 18, 2009 at 3:54pm.

Sn = ln(1 - 1/4) + ln(1 - 1/9) + ln(1 - 1/16) + ... + ln(1 - 1/(n + 1)^2)

-----------------------------

I would guess the first step is this:

e^Sn = (1 - 1/4) * (1 - 1/9) * (1 - 1/16) * ... * (1 - 1/(n + 1)^2)

But how to I conver that to closed form?

- Math (Series) -
**Reiny**, Wednesday, March 18, 2009 at 5:20pmgreat idea to start, now

change each of the brackets to a single number, so you would have

Sn = ln[3/4 * 8/9 * 15/16 * 24/25 * 35/36 + ... ]

let's start multiplying these

P1 = 3/4

P2 = (3/4)(8/9) = 2/3

P3 = (3/4(8/9)(15/16) = 5/8

P4 = (3/4(8/9)(15/16)(24/25) = 3/5

P5 = .... = 7/12

now take a closer look at

3/4, 2/3, 5/8, 3/5, 7/12, ...

or

3/4, 4/6, 5/8, 6/10, 7/12, ... AHHH

so Pn = (n+2)/(2n+2)

Then Sn = ln[(n+2)/(2n+2)]

or e^(Sn) = (n+2)/(2n+2)

hope this is what you were looking for, if not, I enjoyed the manipulation anyway.

- Math (Series) -
**Sean**, Wednesday, March 18, 2009 at 5:47pmThanks so much Reiny! That's the right answer. I've been struggling with it for a few hours. Here's a slightly different route to the same answer:

S_{n}= Π (1 to n) of (1 - 1/(k + 1)^2)

= Π (1 to n) of (k^2 + 2k)/(k + 1)^2

Since

Π of X * Y = Π X * Π Y

and

Π (1 to n) of k = n!

and

Π (1 to n) of (k + a) = (n + a)!/a!

Π (1 to n) of (k^2 + 2k)/(k + 1)^2

= (Π k) * (Π k + 2) * (Π 1/(k + 1)) * (Π 1/(k + 1))

= n! * (n + 2)!/2 * 1/(n + 1)! * 1/(n + 1)!

= 1/2 * (n + 2) / (n + 1)

- Math (Series) -
**Sean**, Wednesday, March 18, 2009 at 5:48pmThat's e^S

_{n}... Not S_{n}...

**Related Questions**

Math - What does the following infinite series starting at k=2 converge to: &...

Help, Math. - Solve: 3e2x + 2 = 50 a. ln 8 b. ln 0.25 c. ln 14 d. 0.5ln 16...

Math differentiation - 1. y = x^x 2. y = (sin^2xtan^4x)/(x^2+1)^2 3. y = x^(1/x...

Calculus!!! - I need your help... I've posted this question a while ago but no ...

Math - ln x^2(x+1)/x+2 Write in terms of ln(x), ln(x+1), and ln(x+2) is the ...

Math - Which equation is equivalent to 3 ln 2 – ln 4 + 5 ln x = ln 3 + 2 ln 5? ...

Math - Which equation is equivalent to 3 ln 2 – ln 4 + 5 ln x = ln 3 + 2 ln 5? ...

math - Express y as a function of x. C is a positive number. 3 ln y= 1/2ln (2x+1...

Math - Given the axioms: ln x = definite integral from 1 to x of 1/t dt ln e = 1...

Calculus - For what values of p>0 does the series Riemann Sum [n=1 to ...